Construction of Simple Bathing, Washing, and Toilet Facilities for Sanitation and Environmental Conservation in Polaman Sub-Village, Kalirejo Village, Lawang District, Malang Regency - Suhartanto, Ery; Bisri, Mohammad; Andawayanti, Ussy; Wahyuni, Sri; Chandrasasi, Dian; Marsudi, Suwanto; Rubiantoro, Prasetyo (TEKAD : Teknik Mengabdi, 2026)
Limited access to adequate bathing, washing, and toilet facilities (MCK) remains a significant problem for residents of RT-03/RW-10, Polaman Sub-Village, Kalirejo Village, Lawang District, Malang Regency, so that some residents still use the river to meet their basic sanitation needs, potentially reducing their health and environmental quality. This Community Service Activity aims to provide simple WASH facilities that meet sanitation standards while promoting behavioral changes toward clean and healthy living through community participation. The implementation methods included an initial survey and interviews to identify the socio-cultural and environmental conditions, discussions to develop solutions with the RT administrators and residents, socialization with the PKK women's group, the construction of the MCK through the self-help efforts of students, donors, and the community during July-October 2025, and an evaluation in November 2025 through field observations, interviews, and documentation. The results of the activity include the construction of a simple, functional, and easy-to-operate toilet two units with a layout that meets comfort standards and better manages wastewater flow; increased community understanding of the importance of sanitation and environmental conservation; and a stronger spirit of cooperation in maintaining shared facilities. Overall, this program was deemed effective by residents and neighborhood association administrators in improving access to basic sanitation, reducing dependence on rivers as a means of sanitation, and supporting the creation of a cleaner, healthier, and more sustainable residential environment, while also providing a model for simple sanitation facilities that can be replicated in similar areas.